Relationship Between N-AFLD and Serum Uric Acid Levels in Non-Diabetic and Non- Obese Adults - Gültekin Pekcan; Hüseyin Demirci; Fahri Yakaryılmaz (Gazi Medical Journal)
Objective: Many studies are interested in the association between non-alcoholic fatty liver disease (N-AFLD) and other parameters. Our study evaluated the association between serum uric acid (SrUA) levels and N-AFLD in non-diabetic non-obese adults. Methods: In this study, 50 patients and 50 control subjects were enrolled to investigate the association between SrUA and N-AFLD in adults. The Kruskal-Wallis test was used to compare SrUA values according to ultrasonographic liver fat levels. Results: A statistically significant difference was found between the N-AFLD and control subjects according to the mean SrUA level (p<0.001). In the N-AFLD group, a positive relationship was found between SrUA levels and homeostasis model assessment of insulin resistance values (r=0.35, p<0.001). Conclusion: In this study, an important positive relationship was detected between SrUA levels and N-AFLD and insulin resistance.